Design and implementation of a DC-DC buck converter with Type III compensator control - Fahmizal, Fahmizal; Sahiddin, Muhammad Rizal; Herlambang, Priyo; Sentana, Gibran Nabil; Maghfiroh, Hari (National Research and Innovation Agency, 2025)
This paper presents a low-cost hardware realization of a Type III compensated DC–DC buck converter with experimental validation under practical load conditions. The compensator is designed using MATLAB Bode plot analysis to achieve the target phase margin, and the resulting pole–zero configuration is verified through LTspice simulation before implementation on a microcontroller-based hardware prototype. Performance testing is conducted under both resistive and DC motor loads to evaluate improvements over an open-loop configuration. Experimental results show that the proposed closed-loop design significantly accelerates transient recovery, reducing settling time from 85–134 ms in the open-loop system to 0.39–5.2 ms in the compensated system, representing improvements of up to two orders of magnitude depending on the load. The closed-loop converter also achieves tighter steady-state regulation around 6 V and smaller effective voltage dips during load transients, confirming the effectiveness of the Type III compensator in enhancing both dynamic and steady-state performance. The implementation demonstrates a practical and cost-efficient approach for applying Type III compensation on low-cost hardware platforms suitable for educational and prototype-level power electronics applications.